Trust Dynamics in Peer-to-Peer Lending : Analyzing Determinants og Willingness to Lend in Indonesia - Simanjuntak, Megawati; Ninuk , Purnaningsih; Zaky , Abdullatif (Universitas Semarang, 2025)
The funding of P2P was relatively small, due to a significant gap between the number of lenders and borrowers. Therefore, analyzing trust determinants that affect the willingness to invest in P2P is required to formulate strategies to increase funding. This study aims to analyze the effects of trust determinants divided into trust on the borrowers and trust on the intermediaries on willingness to lend in P2P lending platforms in Indonesia. An online questionnaire was completed by 109 people. The results showed that trust in borrowers had a significant impact on the willingness to lend. On the other hand, trust in intermediaries does not significantly affect the willingness to lend but significantly affects trust in borrowers. The most important attribute to increase willingness to lend is the borrowers’ trustworthiness, protection system/policy adopted in P2P, sense of security when making transactions in P2P, attractive investment returns, and quality assurance for prospective borrowers.